Musculoskeletal symptoms in nursing students: concept analysis - Cristiana Furtado Firmino; Luís Manuel Mota Sousa; Joana Mendes Marques; Ana Vanessa Antunes; Fátima Mendes Marques; Celeste Simões
ABSTRACT Objective: to analyze the musculoskeletal symptomatology concept in undergraduate nursing students through Rodgers' evolutionary method. Method: An integrative review of the literature was performed for the identification and selection of ten articles. A concept analysis was performed according to Rodgers' evolutionary method. Article search was performed using the EBOSCO Host platform, Virtual Health Library and Google scholar for the years from 2004 to 2018. Results: Based on the 3 elements of Rodgers model we found: 1) substitute terms and related concepts, where musculoskeletal disorders and musculoskeletal symptoms were highlighted; 2) as essential attributes of the concept we highlight pain and discomfort, as well as, measurement using the Nordic Musculoskeletal Questionnaire; and 3) risk factors were identified as antecedents, and the consequences were the impact on students' lives. Conclusions: This study contributes to the knowledge and clarification of the concept of musculoskeletal symptomatology in nursing students.